Genetic diversity and antibiogram profile of diarrhoeagenic Escherichia coli pathotypes isolated from human, animal, foods and associated environmental sources. Issue 1 (1st January 2016) - Dhaka, Pankaj; Vijay, Deepthi; Vergis, Jess; Negi, Mamta; Kumar, Manesh; Mohan, Vysakh; Doijad, Swapnil; Poharkar, Krupali V.; Malik, Satyaveer Singh; Barbuddhe, Sukhadeo Baliram; Rawool, Deepak B.
Abstract : Introduction: Infectious diarrhoea particularly due to pathogenic bacteria is a major health problem in developing countries, including India. Despite significant reports of diarrhoeagenic Escherichia coli (DEC) pathotypes around the globe, studies which address genetic relatedness, antibiogram profile and their correlation with respect to their isolation from different sources are sparse. The present study determines isolation and identification of DEC pathotypes from different sources, their genetic characterisation, antibiogram profile and their correlation if any. Materials and methods: A total of 336 samples comprising diarrhoeic stool samples from infants ( n =103), young animal ( n =106), foods ( n =68) and associated environmental sources ( n =59) were collected from Bareilly region of India. All the samples were screened by using standard microbiological methods for the detection of E. coli . The identified E. coli were then confirmed as DEC pathotypes using polymerase chain reaction–based assays. Those DEC pathotypes identified as Enteroaggregative E. coli (EAEC) were further confirmed using HEp-2 adherence assay. All the isolated DEC pathotypes were studied for their genetic diversity using pulsed-field gel electrophoresis (PFGE), and antimicrobial susceptibility testing was performed by using disc diffusion method as per Clinical Laboratory Standards Institute guidelines. Results and discussion: Of the four DEC pathotypes investigated, EAEC was found to be the predominant pathogen with an isolation rate of 16.5% from infants, 17.9% from young animals, 16.2% from foods and 3.4% from the associated environmental sources. These EAEC isolates, on further characterisation, revealed predominance of 'atypical' EAEC, with an isolation rate of 10.7% from infants, 15.1% from young animals, 16.2% from foods, and 3.4% from the associated environmental sources. On PFGE analysis, discrimination was evident within DEC pathotypes as 52 unique pulsotypes were observed for 59 recovered DEC pathotypes. However, a few EAEC isolates were found to be clonal (clusters A, B, C, D, F, G, and H) irrespective of their source of isolation, suggests sharing and/or circulation among different sources. Further, a high antibiotic resistance pattern was observed among isolated DEC pathotypes as almost 86.4% of isolates were found to be resistant against ≥3 tested drugs.